Comparison of the Effects of Ezetimibe-Statin Combination Therapy on Major Adverse Cardiovascular Events in Patients with and without Diabetes: A Meta-Analysis - Hong, Namki (Endocrinol Metab (Seoul), 2018)
BACKGROUND: Ezetimibe-statin combination therapy has been found to reduce low density lipoprotein cholesterol levels and the risk of major adverse cardiovascular events (MACEs) in large trials. We sought to examine the differential effect of ezetimibe on MACEs when added to statins according to the presence of diabetes. METHODS: Randomized clinical trials with a sample size of at least 50 participants and at least 24 weeks of follow-up that compared ezetimibe-statin combination therapy with a statin- or placebo-controlled arm and reported at least one MACE, stratified by diabetes status, were included in the meta-analysis and meta-regression. RESULTS: A total of seven trials with 28,191 enrolled patients (mean age, 63.6 years; 75.1% men; 7,298 with diabetes [25.9%]; mean follow-up, 5 years) were analysed. MACEs stratified by diabetes were obtained from the published data (two trials) or through direct contact (five trials). No significant heterogeneity was observed among studies (I(2)=14.7%, P=0.293). Ezetimibe was associated with a greater reduction of MACE risk in subjects with diabetes than in those without diabetes (pooled relative risk, 0.84 vs. 0.93; P(heterogeneity)=0.012). In the meta-regression analysis, the presence of diabetes was associated with a greater reduction of MACE risk when ezetimibe was added to statins (β=0.87, P=0.038). CONCLUSION: Ezetimibe-statin combination therapy was associated with greater cardiovascular benefits in patients with diabetes than in those without diabetes. Our findings suggest that ezetimibe-statin combination therapy might be a useful strategy in patients with diabetes at a residual risk of MACEs.